Osteomuscular disorders in care of elderly household people: Prevalence and its associated factors (Research, Society and Development, 2021)
The aim of this study was to estimate the prevalence of more frequent musculoskeletal disorders in caregivers of elderly households and their associated factors. Methodology: quantitative, cross-sectional study, with caregivers of domiciled elderly, 40 formal and informal caregivers participated in the research. Closed interviews were conducted using the Nordic Musculoskeletal Questionnaire, Barthel Index, form for surveying sociodemographic data with characteristics of the caregiver, observation diary with images, individual protection tools and transfer facilitators, a digital scale and a measuring tape. With data collected, a database was built in an electronic spreadsheet that was analyzed in the SPSS program (Statistical Package for the Social Science), version 22.0 and by the Microsoft Excel 2007 application. Results: 97.5% of the caregivers, presented musculoskeletal symptoms in at least least one part of the body in the last 12 months.